Down-regulated notch signaling in arpe-19 cells Cultured on denuded human Amniotic membrane - LEKSHMI KRISHNA; SAMANTA SEKHAR KHORA; DEBASHISH DAS (International Journal of Pharma and Bio Sciences, 2017)
Denuded human amniotic membrane is widely proposed to be used for retinal pigment epithelial cell transplantation. Notch signaling though important and known to have role in both health and disease of retinal pigment epithelial cells; is not well studied for retinal pigment epithelial cells cultured on denuded human amniotic membrane. The outcome of Notch signals is strictly dependent on the cellular level and can influence differentiation, proliferation and apoptotic cell fates. We have studied the regulation of Notch signaling in human retinal pigment epithelial cells (ARPE-19) cultured on denuded human amniotic membrane using gene expression and immunofluorescence analysis. Results revealed a significant down regulation in the levels of NOTCH 3, 4 receptors, DELTA-LIKE 1, 4, JAGGED 1, 2 ligands and HES 3, HES 5 and HEY 1 downstream targets in cells cultured on denuded human amniotic membrane. It can be concluded that human retinal pigment epithelial cells cultured on denuded human amniotic membrane revealed lower Notch activity in comparison to those cultured on tissue culture dish. These findings might provide an initial insight in the signaling modulations of retinal pigment epithelial cells cultured on denuded human amniotic membrane.